Hydroxyapatite Coating on New Type Titanium, TNTZ, Using Electrophoretic Deposition - Nuswantoro, Nuzul Ficky; Maulana, Imron; Tjong, Djong Hon; Manjas, Menkher; Gunawarman, Gunawarman (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2018)
In order to improve bioactivity of new type of titanium alloy, TNTZ, Hydroxyapatite (HA) coating is applied. Electrophoretic Deposition (EPD) has chosen as coating method because the simplicity of the instrument and its making, inexpensive cost, and ability to coat things with complicated design. EPD used electric current to move the HA particle through electrode in the suspension of ethanol and HA. Desired HA coating quality can be adjusted with optimizing the voltage and coating time. This research aimed to analyzed the effect of voltage and coating time of EPD process toward the HA coating that produced on the surface of new type titanium implant prototype, Ti-29Nb-13Ta-4.6Zr (TNTZ). Voltages are in range of 3, 5, and 7 volt and coating times are in range of 3, 5, and 7 minutes. Based on the result it is known that the best HA coating that can be produced are on 7 minutes and 7 volt. This best result shows the good surface morphology, highest value of screw mass growth, coating thickness, and surface coverage. Enhancement of voltage will affect the surface coverage value of HA coating, however, coating time will affect the thickness. Based on this research it can be concluded that enhancement of the voltage can produced HA coating that spread more evenly that proved by the increasing of surface coverage value. The enhancement of coating time will produce thicker layer of HA coating and increase deposition rate of HA on the implant surface. This result shows that the EPD can be used to produce TNTZ titanium implant that coated with HA for orthopedic application.